2022
DOI: 10.1038/s42255-022-00558-0
|View full text |Cite|
|
Sign up to set email alerts
|

The gut microbial metabolite formate exacerbates colorectal cancer progression

Abstract: The gut microbiome is a key player in the immunomodulatory and protumorigenic microenvironment during colorectal cancer (CRC), as different gut-derived bacteria can induce tumour growth. However, the crosstalk between the gut microbiome and the host in relation to tumour cell metabolism remains largely unexplored. Here we show that formate, a metabolite produced by the CRC-associated bacterium Fusobacterium nucleatum, promotes CRC development. We describe molecular signatures linking CRC phenotypes with Fusoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 77 publications
3
114
0
Order By: Relevance
“…Fn reportedly activates Wnt signaling [ 8 ] and produces CSC characteristics and a mesenchymal phenotype in CRC cells [ 17 , 18 ]. The results depicted in Figure 3 complement this information, showing that, although constitutively active, the Wnt cascade can be further stimulated by Fn in CSC, as revealed by the increased inhibitory phosphorylation of the β-catenin destruction factor GSK3β [ 31 ] and by the induction of TCF/LEF-driven recombinant GFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fn reportedly activates Wnt signaling [ 8 ] and produces CSC characteristics and a mesenchymal phenotype in CRC cells [ 17 , 18 ]. The results depicted in Figure 3 complement this information, showing that, although constitutively active, the Wnt cascade can be further stimulated by Fn in CSC, as revealed by the increased inhibitory phosphorylation of the β-catenin destruction factor GSK3β [ 31 ] and by the induction of TCF/LEF-driven recombinant GFP.…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, known that colorectal-tumor-initiating cells exploit autocrine cytokine-triggered circuitries to resist chemotherapy-induced cell death [ 15 ], and that normal intestinal stem cells express innate immune receptors that mediate protection from oxidative damage and ROS cytotoxicity in response to bacterial components [ 16 ]. Additionally, Fn induces CSC-like traits in cultured CRC lines via epithelial–mesenchymal transition (EMT) [ 17 ], and the Fn -derived metabolite formate enhances the stemness and self-renewal capacity of patient-derived colorectal tumor organoids [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest carboxylic acid (formic acid) and its conjugate base (formate) are normal products of metabolic activity in living organisms, including bacteria and humans . However, formate derived from human gut microbiota metabolism drives inflammatory dysbiosis and progression of colorectal cancer . Although formic acid is primarily used as a food preservative (E236) or as a silage additive for maintaining the nutritive value of animal feed, it is a highly sought-after electron-mediator and feedstock in (electro)­microbial bioproduction, as well as a low carbon-footprint molecule that serves as a chemically robust hydrogen storage medium. , In addition to being a carbon and energy source for the anaerobic and aerobic growth of disparate bacteria, archaea, , and syntrophic consortia, formate can be generated abiotically from CO 2 and renewable electricity …”
Section: Introductionmentioning
confidence: 99%
“…The results of a metagenomic analysis found that F. nucleatum proved to be an important marker of colorectal carcinogenesis and tumor aggressiveness [ 27 ]. A co-culture of F. nucleatum and CRC cells could increase formate secretion and cancer glutamine metabolism, which drove CRC tumor invasion and proliferation by triggering aryl hydrocarbon receptor (AhR) signaling [ 28 ]. F. nucleatum was associated with the elevation of angiopoietin-like 4 protein (ANGPTL4) expression in CRC cells, thus increasing glycolytic activity, which plays an important role in F. nucleatum colonization and proliferation in CRC [ 29 ].…”
Section: Relationships Between F Nucleatum and Mal...mentioning
confidence: 99%